STUDENTS’ SKILLS AND PROBLEMS IN WRITING RECOUNT TEXT ( A STUDY AT SMP N 18 SURAKARTA ) - Rakhma Kartikasari (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2020)
This research was to describe the skills of students’ to write recount text and to describe the difficulties experienced by students in writing recount text. The students’ works in writing were analized based on five component of writing: organization, content, grammar, vocabulary and mechanics. This research was a descriptive qualitative method. The subject of this research was class VIII H of SMPN 18 Surakarta in 2019/2020 Academic Year. The object of this research was the students’ writing recount text. Technique collected the data used observation, test, and inteview. Technique to analyze the data was used five component scoring by Brown. Based on the result the students’ were still confused to determine words and to describe the past experience and students problem which emerged were choosing the topic, arranging paragraph, and using appropriate vocabulary.Based on this finding the most dominant problem done by students’ was organization with the percentage 67.82%.. The skills of students writing recount text was fair sufficient because the mean score of the students’ was 53.36. Keywords: Writing, recount text, skills, Probelms, A Study